2020
DOI: 10.1177/1934578x20913691
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Constituents From Chaenomeles speciosa

Abstract: Phytochemical investigation of fruits of Chaenomeles speciosa Lindley (Rosaceae) led to the isolation of 20 compounds including 5 flavonoids (1-5), 5 phenylpropanoids (6-10), 3 benzoic acid derivatives (11-13), 2 phloroglucinols (14 and 15), 2 purines (16 and 17), and 3 terpenoids (18–20). Their structures were elucidated by nuclear magnetic resonance analyses and from mass spectrometry data. These compounds were confirmed as catechin (1), epicatechin (2), catechin-5- O-β-d-glucoside (3), procyanidin B1 (4), q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…There are a series of rich chemical contents, including triterpenes, phenolic acids, flavonoids, coumarins, triterpenoids saponins, essential oils, and alkaloids, ,, among which some have already been isolated from this fruit to evaluate their biological activities. A large number of pharmacological studies have shown that this plant possesses anti-inflammatory, antinociceptive, antimicrobial, antioxidant, , immunoregulatory, antiparkinsonian, hepatoprotective, and antitumor characteristics. , However, there are no abundant published reports regarding the mechanism of antimicrobial activity and constituents in bioactivity fractions.…”
Section: Introductionmentioning
confidence: 99%
“…There are a series of rich chemical contents, including triterpenes, phenolic acids, flavonoids, coumarins, triterpenoids saponins, essential oils, and alkaloids, ,, among which some have already been isolated from this fruit to evaluate their biological activities. A large number of pharmacological studies have shown that this plant possesses anti-inflammatory, antinociceptive, antimicrobial, antioxidant, , immunoregulatory, antiparkinsonian, hepatoprotective, and antitumor characteristics. , However, there are no abundant published reports regarding the mechanism of antimicrobial activity and constituents in bioactivity fractions.…”
Section: Introductionmentioning
confidence: 99%